Institution Based Industry and MSME Synergy in Improving National Industrial Competitiveness: Implementation and Transmission Schemes - Yasin, Mohammad Zeqi; Yanuarisma, Intan (Jurnal Ilmu Ekonomi Terapan, 2016)
This study aims to determine the level of efficiency of the industry in Indonesia, build synergy concept of industrial and institutional-based Micro, Small, Medium Enterprises (MSME) in Indonesia and analyze the effect of synergy transmission industry and MSME to Public Private Partnership to improve infrastructure development in Indonesia. The method used to answer the purpose of this research is the method of Data Envelopment Analysis (DEA) and descriptive study. Referring to the Cobb-Douglas models, input variables used are the capital and the capital, while the variable output that is used is the output of 24 types of industry. The result indicates that the industry condition in Indonesia is slowing down. Deceleration parameters can be seen from the industry's contribution to GDP has decreased. In addition, the increase in PPP due to the increase in industrial efficiency will increase state revenues for infrastructure development in Indonesia